Foliar fertilizer and ripener improve sucrose and bioenergy production by increasing sucrose metabolic enzyme activity in early-harvest sugarcane - Prado Filho, Anibal Pacheco de Almeida [UNESP]; Hervatin, Cleber de Morais [UNESP]; Momesso, Letusa; Jacomassi, Lucas Moraes [UNESP]; Pacola, Marcela [UNESP]; Sartori, Maria Marcia Pereira [UNESP]; Crusciol, Carlos Alexandre Costa [UNESP] (CSIRO Publishing, 2025)
Context Innovative sugarcane management with foliar multinutrient fertilizers and ripeners can increase global production of renewable fuels, sugar, and energy by improving plant growth, sucrose accumulation, and yield. However, the combined effects and timing remain unclear. Aims This study evaluated the impact of foliar multinutrient fertilizer and ripener application, alone or together, on sugarcane growth, quality, yield, and enzymatic activities. Methods Eight treatments combining foliar fertilization at vegetative and/or maturation stages with or without ripener (control, V, M, VM, R, VR, MR, and VMR) were assessed in 18 field experiments at 10 sites in southern-central Brazil over three seasons, by using a randomized block with four replicates design. Data on growth metrics, enzymatic activities, and sugar production were analyzed by ANOVA and the Scott–Knott test. Key results Growth metrics were highest when foliar fertilization occurred at the vegetative stage, with or without ripener. The V, VM, VR, and VMR treatments increased stalk yield by 7.2, 10.5, 5.9, and 9.2 Mg ha−1 respectively, compared with the control. Ripener application increased recoverable sugar by 7.2 kg Mg stalk−1, whereas combined fertilizer and ripener application boosted sugar yield by 2.1 Mg ha−1 and energy production by 7.8%. Neutral invertase and sucrose synthase activities were highest and lowest respectively, in the VMR treatment. Conclusions Combining foliar fertilization at vegetative and maturation stages with ripener application is an effective strategy to enhance sugarcane growth, yield, and sucrose metabolism. Implications This combined approach can improve sugarcane management yield and sustainability in bioenergy and sugar industries.